2019
DOI: 10.1080/13696998.2019.1658591
|View full text |Cite
|
Sign up to set email alerts
|

Febrile neutropenia hospitalization due to pegfilgrastim on-body injector failure compared to single-injection pegfilgrastim and daily injections with reference and biosimilar filgrastim: US cost simulation for lung cancer and non-Hodgkin lymphoma

Abstract: Abraham (2020) Febrile neutropenia hospitalization due to pegfilgrastim on-body injector failure compared to single-injection pegfilgrastim and daily injections with reference and biosimilar filgrastim: US cost simulation for lung cancer and non-Hodgkin lymphoma,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…For example, the potential cost associated with patient hospitalization due to a missed dose of medication should be weighed in the patient management decision. 24 An additional factor is whether the device has a clear indicator of error and therefore can be easily monitored. The on-body injector device has both visual and audible error indicators.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the potential cost associated with patient hospitalization due to a missed dose of medication should be weighed in the patient management decision. 24 An additional factor is whether the device has a clear indicator of error and therefore can be easily monitored. The on-body injector device has both visual and audible error indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Although the cost ratio in CMA studies could be quantified specific to each patient per cycle, it's hard to compare them directly, like the cost ratios for G-CSF biosimilars. Apart from the coverage region, study design, such as retrospective cohort in the hospital setting (Ianotto et al, 2014;Bongiovanni et al, 2017) and hypothetical cohort (Mehta and Hay, 2014;Sun et al, 2015;McBride et al, 2017;McBride et al, 2020), and data source for cost, including the hospital base and official database, would contribute the variation together. Besides, under the market with multi-stakeholders, cost for biosimilars would concern the drug itself, administration and condition (McBride et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 17 studies were finally included in this study, and the detailed information is displayed in Figure 1 (Aapro et al, 2012a;Aapro et al, 2012b;Nikolaidi et al, 2013;Abraham et al, 2014;Ianotto et al, 2014;Mehta and Hay, 2014;Sun et al, 2015;Valentina et al, 2016;Bongiovanni et al, 2017;Cesarec and Likić, 2017;Gulácsi et al, 2017;McBride et al, 2017;Rognoni et al, 2018;Giuliani and Bonetti, 2019;Lee et al, 2019;Trautman et al, 2019;McBride et al, 2020). All included studies were published in last decade, of which 8 studies were reported in the recent three years.…”
Section: Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations